2014
DOI: 10.1016/j.bbadis.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of motives mediating alternative functions of the neomorphic moonlighting TPPP/p25

Abstract: The disordered Tubulin Polymerization Promoting Protein (TPPP/p25), a prototype of neomorphic moonlighting proteins, displays physiological and pathological functions by interacting with distinct partners. Here the role of the disordered N- and C-termini straddling a middle flexible segment in the distinct functions of TPPP/p25 was established, and the binding motives responsible for its heteroassociations with tubulin and α-synuclein, its physiological and pathological interacting partner, respectively, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(78 citation statements)
references
References 35 publications
(62 reference statements)
8
70
0
Order By: Relevance
“…Earlier we showed that the 147 KAPIISGVTK 156 segment of the flexible CORE region of TPPP/p25 is involved in the formation of the pathological TPPP/p25-SYN complex, while the 178-187 segment of the C-terminus takes part in the formation of the physiological TPPP/ p25-tubulin/microtubule complex [35]. Deletion and/or truncated variants and fragments of the human TPPP/p25 were produced by recombinant techniques as described in the Materials and Methods and used for structural and functional studies.…”
Section: Generation Of Deletion Mutants Of Tppp/p25mentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier we showed that the 147 KAPIISGVTK 156 segment of the flexible CORE region of TPPP/p25 is involved in the formation of the pathological TPPP/p25-SYN complex, while the 178-187 segment of the C-terminus takes part in the formation of the physiological TPPP/ p25-tubulin/microtubule complex [35]. Deletion and/or truncated variants and fragments of the human TPPP/p25 were produced by recombinant techniques as described in the Materials and Methods and used for structural and functional studies.…”
Section: Generation Of Deletion Mutants Of Tppp/p25mentioning
confidence: 99%
“…Recently we have suggested a new strategy for the therapeutic treatment of Parkinson's disease by targeting the interface of the pathological TPPP/p25-SYN complex without influencing the physiological interaction of TPPP/p25 with tubulin/microtubules [35,36]. The distinct interface of the physiological and pathological complexes is a crucial point in our drug targeting strategy.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 3 more Smart Citations